Numerical Analysis on a Double Pipe Heat Exchanger with Twisted Tape Induced Swirl Flow on Both Sides. (2016) - Ranjith; Shaji, K.
Abstract: Twisted tape inserts are widely used for enhancing heat transfer in heat exchangers. They enhance heat transfer by inducing swirl flow in the flow channel, thereby enabling good mixing within the fluid and by increasing the effective flow length of the flow channel. They also increase pressure drop but their overall performance is found to be advantageous in many cases. In this work, an attempt is made to analyse the performance of a modified double pipe heat exchanger with twisted tape induced swirl flow on both sides. The numerical analysis were done in turbulent flow conditions with twisted tape inserts of twist ratio 5 and 3. The results obtained are validated using established correlations available in the literature. The fin effect of twisted tape is also discussed.